Revealing multi-scale characteristics of ecosystem services supply and demand imbalance to enhance refined ecosystem management in China - Mengwen Gao; Yecui Hu; Xinwei Liu; Mengyin Liang (Ecological Indicators)
Spatial heterogeneity in the supply and demand of ecosystem services across multi spatiotemporal scales facilitates the formulation of ecosystem management policies at diverse administrative levels. We mapped the five ecosystem services (ESs) in China, analyzed the spatiotemporal evolution of ESs supply and demand pattern from 2000 to 2020, revealed the spatial distribution patterns and trade-off synergies of ecosystem services supply–demand ratio (ESDR) at multiple scales. Additionally, we explored ecosystem sustainable management pathways adapted to different scales of grid, city and basin. The results showed that, except for soil conservation, significant supply–demand imbalances existed in the other four ESs, with obvious deficits in food supply and water yield. Spatial clustering of ESDR slight variations in refinement level and regional synergy at different scales, with high-value predominantly observed in the southeast, low-value areas in the northwestern region. The increase of high-high (H-H) clustering units at the city and basin scales indicated an overall improvement in supply–demand imbalances on a larger scale. Moreover, the scale dependence of interactions between ESDRs was obvious. At the grid scale, most ESDRs exhibited a synergistic relationship with the strongest intensity. At the city scale, supply–demand ratio of food supply showed significant trade-offs with other types of ESDRs, and this effect was significantly weakened at the basin scale, even tended to shift toward synergistic effects. Consequently, this study suggested that the ESs supply–demand relationship should focus on multiple-scale dependence, enabling the effective design of refined ecosystem management strategies.